Therapeutic Response of Alopecia Areata-Associated Nail Changes to Baricitinib - Ashley Wittmer; Katherine De Jong; Lauren Bolish; Lindsey Finklea (Hindawi Limited, 2024)
Nail changes are seen in some individuals with alopecia areata, with the most common variants including pitting and trachyonychia. The nail findings are presumed to be due to the same lymphocytic infiltration seen in hair bulbs in individuals with AA. Baricitinib is an immunomodulatory drug that acts as a selective and reversible inhibitor of JAK proteins and is indicated for adult patients with moderate to severe rheumatoid arthritis who have not responded to other disease-modifying antirheumatic drugs. The FDA has also approved baricitinib to treat patients hospitalized with COVID-19 and severe alopecia areata. In this report, we present a case of a patient with persistent AA-associated nail changes who has been successfully treated with baricitinib. The patient has been suffering from alopecia for several years. She presented with periungual inflammation in conjunction with persistent fingernail ridges and pitting of her right fourth digit. The nail dystrophy persisted despite treatment with tacrolimus ointment, clobetasol ointment, or oral fluconazole. Patient was started on a trial of baricitinib for alopecia areata, which was the suspected cause of the nail changes. After 4 months of treatment with baricitinib, the patient's nail showed mild improvement of nail dystrophy with some clubbing and pitting still present. Within 11 months of treatment, her nail was normalized in appearance and texture. There are no established guidelines to treat AA-associated nail changes. Our patient's AA-associated nail changes were normalized after 11 months of treatment with baricitinib. Further research is needed to determine which alopecia areata patients may benefit from treatment with baricitinib and when treatment should be initiated. Baricitinib may be an effective treatment option for AA-associated nail changes in some patients.